Evaluation of the effects of long-term storage of bovine ear notch samples on the ability of two diagnostic assays to identify calves persistently infected with bovine viral diarrhoea virus - Van Vuuren, Moritz (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.